Serum adiponectin and metabolic profile in women with polycystic ovarian syndrome in relation to body mass index - Onyegbule, Onyema A.; Meludu, Samuel C.; Dioka, Chudi E.; Okwara, John E.; Obi-Ezeani, Chikaodili N.; Njoku, Chidiadi M. (International Journal of Research in Medical Sciences, 2022)
Background: Polycystic ovarian syndrome is a common endocrine disorder which affects approximately 5-10% of women in reproductive age. It is both a reproductive endocrinopathy and a metabolic disorder. Methods: 160 women aged 18 to 40 years attending obstetrics and gynaecology clinic at Federal medical centre, Owerri, Imo State Nigeria were recruited and divided into 2 groups (women diagnosed with PCOS using Rotterdam criteria and control) of 80 participants each. Anthropometric data were collected, and participants categorized into 3 based on BMI. Fasting blood samples was collected for biochemical analyses. Data were analyzed using the Statistical Package for Social Sciences SPSS version 23.0, and level of significance set at p<0.05. Results: The mean serum levels of adiponectin and high density lipoprotein (HDL-C) were significantly lower while fasting plasma glucose, serum insulin, homeostatic model assessment for insulin resistance, total cholesterol, low density lipoprotein (LDL-C), very low density lipoprotein (VLDL-C) and triglyceride were significantly higher in women with PCOS when compared with the control (p<0.05) as well as in obese when compared with normal weight women with PCOS (p<0.05). BMI negatively correlated with serum adiponectin and HDL-C, but positively correlated with FPG, insulin, HOMA-IR, TC, TG, LDL-C and VLDL-C in women with PCOS (p<0.05). Conclusions: This study highlights the prevalent biochemical and metabolic derangements in PCOS patients and was more evident in the obese and overweight patients. Early detection with subsequent application of preemptive measures including lifestyle modifications are therefore essential in the management of PCOS patients.